Effects of Adding Adenosine Triphosphate to Semen Diluter on Quality of Spermatozoa of Fat-Tailed Sheep - Pramono, E; Tagama, TR (ANIMAL PRODUCTION, 2008)
The research aimed to investigate the effects of adding different levels of Adenosine Triphosphate (ATP) to semen diluter on quality of sperms of fat-tailed sheep. Treatments consisted of 5, 10 and 15 mg of ATP addition into semen diluter (Egg Yolk Sodium Citric). Results showed that treatments have no significant effects on spermatozoa motility, significant effects on spermatozoa viability, and high significant effects on spermatozoa mortality.  On average, sperm motility for control was 79.16 ± 3.99%; ATP 5 mg = 84.13 ± 5.36%; ATP 10 mg = 85.16 ±  4.54%; and ATP 15 mg = 85.33 ± 3.79 %; sperm viability for control was 25.28 ± 0.49; ATP 5 mg = 26.17 ± 1.53; ATP 10 mg = 27.56 ± 1.48; and ATP 15 mg = 28.34 ± 1.03 (hours); sperm mortality for  control was 12.91 ± 1.05%; ATP 5 mg = 15.59 ± 5.12%; ATP 10 mg = 21.95 ± 2.32%; and ATP 15 mg = 22.25 ± 1.83 %; and quality of sperm for control was 198.216 ± 5.65; ATP 5 mg= 206.312 ± 5.67; ATP 10 mg = 208.164 ± 5.14; and ATP 15 mg = 207.104 ± 5.90.  It can be concluded that addition of ATP into semen diluter was able to increase spermatozoa viability. (Animal Production 10(3): 151-156 (2008) Key Words: Fat-tailed sheep, spermatozoa, viability, diluter